Stabilization and Solidification of Hazardous, Radioactive, and Mixed Wastes: 2nd Volume 1992
DOI: 10.1520/stp19554s
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Attack of Pure Water or Undersaturated Lime Solutions on Cement

Abstract: A simplified model of cement attack by pure water or undersaturated lime solutions is proposed for long-term predictions of concrete degradation. The degradation is modeled by ionic diffusion in the cement pores coupled with mass exchange between the solid and aqueous phases. The local equilibrium hypothesis is discussed and justified for the present application. The only solid phases taken into account are portlandite [Ca(OH)2] and calcium-silicate-hydrate (C-S-H). The model predicts the existence of an undam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 9 publications
0
17
0
3
Order By: Relevance
“…As for the thermodynamic equilibrium of calcium in the solid and liquid phases, an isotherm correlation proposed by Buil's et al (1992) is installed with minor modifications for computational efficiency as shown in Fig. 3.…”
Section: Solid-liquid Equilibrium For Calciummentioning
confidence: 99%
“…As for the thermodynamic equilibrium of calcium in the solid and liquid phases, an isotherm correlation proposed by Buil's et al (1992) is installed with minor modifications for computational efficiency as shown in Fig. 3.…”
Section: Solid-liquid Equilibrium For Calciummentioning
confidence: 99%
“…In considering diffusion phenomena related to the long-term durability of cementitious materials, ion diffusion models have been proposed in studies on numerical analysis (Buil et al 1992;Sutou et al 2004). It is generally known that the diffusion coefficient is high in correlation with the void ratio when the chemical influence of hydration products and layered compounds is supposed to be small.…”
Section: Validity Of Application Of Electrical Treatment For Leachingmentioning
confidence: 99%
“…Numerical analysis of deterioration caused by leaching has been reported (Buil et al 1992;Sutou et al 2004). Reports have described modeling of dissolution from the solid phase and ion diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…3 (Buil et al 1992). The initial concentration of Ca 2+ in the pore solution is 0.02 mol/l-solution and must be maintained as long as the Ca(OH) 2 remains in the solid.…”
Section: Chemical Equilibrium For Ca(oh) 2 Dissolution and C-s-h Decamentioning
confidence: 99%